Clinical factors of development of squamous intraepithelial cervical lesions of high grade in patients with papillomavirus infection - T. A. Dimitriadi; D. V. Burtsev; E. A. Dzhenkova (Исследования и практика в медицине, 2020)
Purpose of the study. To assess the chances of development of squamous intraepithelial cervical lesions of high degree (H‑SIL) in patients infected with human papillomavirus (HPV).Patients and methods. 75 HPV positive patients. The main group — with a histological diagnosis of H‑SIL (n=50), the control group — with a histological diagnosis without H‑SIL (n=25). Liquid-based cytology, colposcopy, cervical excision; HPV test, diagnosis of sexually transmitted infections — PCR in real time; a comprehensive bacteriological study. Assessment tool interconnections — odds ratio, categorical data analysis — statistical packages STATISTICA 6.0 and SPSS 22 "Statistical Package for the Social Sciences".Results. In the age group up to 30 years, the chances of H‑SIL development are 26 times higher, 30–40 years — 38 times higher compared to patients over 50 years (p<0.05). With a menstrual cycle of more than 35 days, the chances of H‑SIL development are 71 times greater than in patients with a normal menstrual cycle (p<0.05).Comparison of the chances of the presence of abnormal colposcopic patterns — the presence of significant lesions related to the II degree of colposcopic changes increases the chances of H‑SIL 8.4 times compared to the normal colposcopic pattern. The chances of development of H‑SIL in patients with colposcopy results of minor lesions (I degree), do not differ from those who have a normal colposcopic picture (p>0.05). The presence of chronic inflammatory diseases of the pelvic organs. Earlier treatment of cervical diseases by destruction reduces the risk of H‑SIL 0.08 times. The presence of chronic diseases of the pelvic organs increases the risk of H‑SIL 24 times (p<0.05).Conclusion. The group at greatest risk of having H‑SIL -women 30–40 years, whose menstrual cycle is more than 35 days, with significant lesions according to the results of colposcopic examination, chronic diseases of the pelvic organs, which had not previously been carried out destruction of the cervix.